2016
DOI: 10.3748/wjg.v22.i40.8883
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological and clinical aspects of gastric hyperplastic polyps

Abstract: Gastric polyps become a major clinical problem because of high prevalence and tendency to malignant transformation of some of them. The development of gastric hyperplastic polyps results from excessive proliferation of foveolar cells accompanied by their increased exfoliation, and they are macroscopically indistinguishable from other polyps with lower or higher malignant potential. Panendoscopy allows detection and differentiation of gastric polyps, usually after obtaining histopathological biopsy specimens. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
51
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 36 publications
3
51
3
5
Order By: Relevance
“…Most polyps in their study were fundus gland polyps (FGPs) and polyps and gender were therefore found to be related; but in the present study, despite the higher prevalence of the female patients, no significant relationship were observed between polyps and gender. The disparity between these two studies may be due to the small sample size used in the present study [8].Most polyps in the present study were in the body of the stomach, which is consistent with the results obtained by Markowski et al, although researchers used to argue that most gastric polyps develop in the antral region [8,9] The most frequent age group affected in this study was the over-60 age group, which is inconsistent with the results obtained by Fan N-N et al . (2015) who had found the 45 to 60 age group to be most affected by polyps and had reported the incidence of gastric polyps to reduce after age 60; in the present study, however, the incidence of polyps increased with age [7].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Most polyps in their study were fundus gland polyps (FGPs) and polyps and gender were therefore found to be related; but in the present study, despite the higher prevalence of the female patients, no significant relationship were observed between polyps and gender. The disparity between these two studies may be due to the small sample size used in the present study [8].Most polyps in the present study were in the body of the stomach, which is consistent with the results obtained by Markowski et al, although researchers used to argue that most gastric polyps develop in the antral region [8,9] The most frequent age group affected in this study was the over-60 age group, which is inconsistent with the results obtained by Fan N-N et al . (2015) who had found the 45 to 60 age group to be most affected by polyps and had reported the incidence of gastric polyps to reduce after age 60; in the present study, however, the incidence of polyps increased with age [7].…”
Section: Discussionsupporting
confidence: 82%
“…Hyperplastic polyps can DOI: 10.9790/0853-1603018790 www.iosrjournals.org 89 | Page be singular or multiple and can present independently of other conditions or concomitant with familial polyposis syndrome [6,7]. In the present study, hyperplastic polyps made up 69.3% of all the reported gastric polyps, which agrees with the results obtained by Markowski AR et al, who reported that, although most gastric polyps in the US are of the fundus type, 25% to 71% of the polyps found in their study were hyperplastic [9]. The incidence of hyperplastic polyps increases with age and they are mostly observed in people over 65 [1,4].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations